2021
DOI: 10.1002/clc.23627
|View full text |Cite
|
Sign up to set email alerts
|

Genetics, its role in preventing the pandemic of coronary artery disease

Abstract: Epidemiologists have claimed for decades that about 50% of predisposition for coronary artery disease (CAD) is genetic. Advances in technology made possible the discovery of hundreds of genetic risk variants predisposing to CAD. Multiple clinical trials have shown that cardiac events can be prevented by drugs to lower plasma low‐density lipoprotein cholesterol (LDL‐C). A major barrier to primary prevention is the lack of markers to identify those individuals at risk prior to the development of symptoms of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Among the former, some major factors to mention are physical activity, diet, smoking habits, obesity, etc. About the latter, information from different studies has recommended a 40–80% genetic link [ 9 , 10 ]. A person with parental history of premature atherosclerosis has a 1.5- to 2-fold risk of developing the same [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the former, some major factors to mention are physical activity, diet, smoking habits, obesity, etc. About the latter, information from different studies has recommended a 40–80% genetic link [ 9 , 10 ]. A person with parental history of premature atherosclerosis has a 1.5- to 2-fold risk of developing the same [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cardiovascular diseases have the highest mortality rate and are the "number one killer" of human beings (Roberts and Fair 2021). Among them, acute cardiovascular diseases such as myocardial infarction (MI) and cerebral infarction (CI) have the high suddenness and lethality (Du et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…39,40 CAD-PRS has greater benefits when implemented in young adults given the limitations of traditional risk factors in identifying the risk of ASCVD at a younger age. 6 Our results indicate higher QALYs gained and cost-savings when PCE+PRS was implemented in a 40-vs 75-year-old cohort, primarily due to the long term benefits from prevention of adverse health outcomes in young adults (Figure 4). Previous work has demonstrated that individuals who receive their genetic results are more likely to report behavior changes.…”
Section: Discussionmentioning
confidence: 75%
“…The pooled cohort equation (PCE) is used to determine an individual's 10-year risk of atherosclerotic cardiovascular disease (ASCVD) but it does not identify all individuals at high risk 1,2 leading to missed opportunies to intervene and prevent adverse health outcomes. Strong evidence shows a substantial proportion of coronary artery disease (CAD) is attributable to genetic factors [3][4][5][6] which are not currently considered in the PCE. The integration of such genetic risk factors into the primary prevention setting remains limited and the cost-effectiveness is unknown.…”
Section: Introductionmentioning
confidence: 99%